Pre-ICU statin therapy reduces 28-day mortality in sepsis-associated brain dysfunction: a propensity-matched analysis of potential neuroprotective mechanisms - Yu, Lei; Zou, Shan; Zheng, Sihao; Deng, Jiangtao; Zhou, Qingshan; Jin, Jun (Frontiers in Pharmacology, 2025)
BackgroundSepsis-associated brain dysfunction (SABD) is a severe complication of sepsis characterized by acute cognitive impairment and altered mental status, contributing to increased morbidity and mortality in intensive care units (ICUs). The pathophysiology involves neuroinflammation, oxidative stress, and blood-brain barrier disruption. Despite evidence suggesting potential anti-inflammatory and antioxidative properties of statins, their neuroprotective effects in SABD patients remain poorly characterized.MethodsThis retrospective cohort study utilized the MIMIC-IV database (version 3.1), including adult ICU patients meeting Sepsis-3.0 criteria and diagnosed with SABD, defined as Glasgow Coma Scale (GCS) score <15 or presence of delirium. Patients with preexisting neurological disorders, chronic alcohol/substance abuse, or severe metabolic imbalances were excluded. Pre-ICU statin use was identified through prescription records. Propensity score matching (PSM) at a 1:1 ratio was performed to balance baseline characteristics between pre-ICU statin users (n = 374) and non-users (n = 374). The primary outcome was 28-day all-cause mortality, with secondary outcomes including ICU mortality, in-hospital mortality, and length of stay. Kaplan-Meier survival analysis and Cox proportional hazards regression models were utilized to assess associations between pre-ICU statin use and clinical outcomes.ResultsAmong 1,463 eligible patients, 412 (28.2%) received pre-ICU statin therapy. After PSM, baseline characteristics were well-balanced between groups. Kaplan-Meier analysis demonstrated significantly higher 28-day survival rates among statin users (91% vs. 85%; P = 0.0051). Cox regression demonstrated that pre-ICU statin use was independently associated with reduced 28-day mortality (HR: 0.604, 95% CI: 0.380–0.960, P = 0.033). Subgroup analyses revealed consistent protective effects in patients aged ≥65 years, males, those requiring vasopressors, and those on mechanical ventilation. Sensitivity analyses confirmed the robustness of these findings. Secondary outcomes showed trends toward reduced ICU mortality and shorter ICU stays in statin users, though these associations did not reach statistical significance after adjustment.ConclusionPre-ICU statin therapy was associated with improved 28-day survival in SABD patients, potentially attributable to anti-inflammatory and antioxidant mechanisms. Despite limitations inherent in its retrospective design, this study suggests that statins may represent a promising therapeutic option for SABD patients. Prospective randomized controlled trials are warranted to validate these findings and optimize treatment protocols for this vulnerable population.